The Dangers of Witchcraft in the View of Hadith: A Study of Takhrij and Hadith Syarah - Pramudyah, Gea; Amin, Azizah Amini binti (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the hadith about the dangers of magic. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the dangers of magic in the history of Malik No. 1564. The results and discussion of this study indicate that the status of hadith is of authentic quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Malik No. 1564 is relevant to be used as motivation, advice, and learning about the dangers of magic.